ANALISIS PENGOLAHAN LIMBAH CAIR DOMESTIK DI PULAU PRAMUKA KABUPATEN KEPULAUAN SERIBU, DKI JAKARTA - Ernamaiyanti, Ernamaiyanti; Yunanda, Mega (Civil Engineering Study Program Faculty of Engineering, University of Palembang, 2023)
Domestic liquid waste can contaminate the soil, damage aquatic ecosystems, affect people's drinking water sources, cause germs of disease and cause unpleasant odors if not managed properly. This study aims to analyze the processing of domestic wastewater on Pramuka Island, Seribu Islands Regency, DKI Jakarta. This study used an observational method regarding waste management and the quality of domestic wastewater. This research was conducted on Pramuka Island, Thousand Islands Regency, DKI Jakarta. From the results of observations regarding the processing of liquid waste, it is described in detail and the quality of the liquid waste will be compared with the Decree of the Minister of State for Environment and Forestry Number 68 of 2016 and Regulation of the Minister of Environment Number 19 of 2010. Laboratory test results and analysis show that the management of Pramuka Island's domestic wastewater meets quality standards, except for the inlet and outlet sampling points of WWTP Zone 3, only the ammonia parameter (NH3-N)+ the measurement results are above the established quality standard.